PSO-Based Optimum Design Of PID Controller for Switching Reluctance Motor - Ekhlas M. Thejeel; Mazin M. Mahdi; Zainab N. Abbass (Engineering and Technology Journal, 2013)
This paper presents simulation results for three phase, 6/4 poles switched reluctance motor (SRM) by using particle swarm optimization (PSO) method for formative the optimal proportional-integral-derivative (PID) controller tuning parameters.The proposed approach has superior feature, including easy implementation, stable convergence characteristics and very good computational performances efficiency. The main focus of this paper is to investigate the dynamic performance of switched reluctance (SR) motors. This investigation is achieved through simulation using MATLAB/SIMULINK. Digital simulation results show that the designed (PSO) have a good dynamic behaviour of the motor, a perfect speed tracking with no overshoot and a good rejection of impact loads disturbance. The results of applying the (PSO) mode controller to a SRM give best performances and high robustness than those obtained by the application of others controller. The obtained results of the closed loop PSO-PID response shows excellent performance with respect to the PID controller.